The impact of COVID-19 infection on hip fractures 30-day mortality. (October 2021) - Fadulelmola, Ahmed; Gregory, Rob; Gordon, Gavin; Smith, Fiona; Jennings, Andrew
Introduction: A novel virus, SARS-CoV-2 has caused a fatal global pandemic which particularly affects the elderly and those with co-morbidities. Hip fractures affect elderly populations, necessitate hospital admissions, and place this group at particular risk from COVID-19 infection. This study investigates the effect of COVID-19 infection on 30-day hip fracture mortality. Method: Data related to seventy-five adult hip fractures admitted to two units during March and April 2020 was reviewed. The mean age was 83.5 years (range 65-98 years) and most (53, 70.7%) were females. The primary outcome measure was 30-day mortality associated with COVID-19 infection. Results: The COVID-19 infection rate was 26.7% (20 patients), with a significant difference in the 30-day mortality rate in COVID-19 positive group (10/20, 50%) compared to COVID-19 negative group (4/55, 7.3%), with mean time to death of 19.8 days (95% confidence interval 17.0-22.5). The mean time from admission to surgery was 43.1 hours and 38.3 hours, in COVID-19 positive and COVID-19 negative groups, respectively. All COVID-19 positive patients had shown symptoms of fever and cough, and all ten cases who died were from hypoxia. Seven (35%) cases had radiological lung findings consistent with viral pneumonitis which resulted in mortality (70% of mortality). 30% (n = 6) contracted the COVID-19 infection in the community and 70% (n = 14) developed symptoms after hospital admission. Conclusion: Hip fractures associated with COVID-19 infection have a high 30-day mortality. COVID-19 testing and chest x-ray for patients presenting with hip fractures, helps in early planning of high-risk surgeries and allows counselling of the patients and family using realistic prognosis.